PENGARUH KOMPETENSI, INDEPENDENSI, TIME BUDGET PRESSURE DAN PENGALAMAN KERJA TERHADAP KUALITAS AUDIT - Basuki Basuki (Universitas Muhammadiyah Tangerang, 2023)
The purpose of this study was to determine the effect of competence, independence, time budget pressure and work experience on audit quality at a Public Accounting Firm in Tangerang City. The methodology used is quantitative using primary data through questionnaires distributed to auditors working at the Public Accounting Firm in Tangerang City. The design of this study uses a causal asosiative. The population in this study are auditors who work at Public Accounting firm in Tangerang City. The sampling technique use convenience sampling totaling 81 respondents. The data used in this study are primary data obtained from questionnaires distributed by researchers to auditors in the Public Accounting Firm in Tangerang City. The data analysis technique used multiple linear regression. The results showed that: (1) the competence had a positive and significant effect on audit quality, (2) independence had a positive and significant effect on audit quality, (3) time budget pressure has a positive and significant effect on audit quality, and (4) work experience has a positive and significant effect on audit quality.